Glycosylation status of serum in inflammatory arthritis in response to anti-TNF treatment. - Collins, Emily S.; Galligan, Marie C.; Saldova, Radka; Adamczyk, Barbara; Abrahams, Jodie L.; Campbell, Matthew P.; Ng, Chin-Teck; Veale, Douglas J.; Murphy, Thomas B.; Rudd, Pauline M.; FitzGerald, Oliver (Rheumatology, 2013)
Objective. Glycosylation is the most common post-translational modification and is altered in disease. The typical glycosylation change in patients with inflammatory arthritis (IA) is a decrease in galactosylation levels on IgG. The aim of this study is to evaluate the effect of anti-TNF therapy on whole serum glycosylation from IA patients and determine whether these alterations in the glycome change upon treatment of the disease.Methods. Serum samples were collected from 54 IA patients before treatment and at 1 and 12 months after commencing anti-TNF therapy. N-linked glycans from whole serum samples were analysed using a high-throughput hydrophilic interaction liquid chromatography-based method.Results. Glycosylation on the serum proteins of IA patients changed significantly with anti-TNF treatment. We observed an increase in galactosylated glycans from IgG, also an increase in core-fucosylated biantennary galactosylated glycans and a decrease in sialylated triantennary glycans with and without outer arm fucose. This increase in galactosylated IgG glycans suggests a reversing of the N-glycome towards normal healthy profiles. These changes are strongly correlated with decreasing CRP, suggesting a link between glycosylation changes and decreases in inflammatory processes.Conclusion. Glycosylation changes in the serum of IA patients on anti-TNF therapy are strongly associated with a decrease in inflammatory processes and reflect the effect of anti-TNF on the immune system.